The Visual Mechanisms of Seeing in Experiencing the Interior - Sengke, Maria M. C.; Mustikawati, Triandriani (UI Scholars Hub, 2019)
This paper discusses the visual mechanisms of seeing and their significance in experiencing an interior space. The discussion investigates what the observers can obtain from seeing activities. The aim is to emphasise on the role of seeing as a way of constructing the relation between human and the interior environment. The paper explores the mechanisms of seeing by focusing on two different ways, which are seeing in a static position from a point of observation, and seeing while moving through a path of observation. The exploration in a hospital setting finds out that seeing from a point of observation gave a visual range determined by the body's shaft motion, head motion, and eye movement. This way of seeing produces visual information on interior space, which consists of vertical and horizontal fields. Seeing while moving will create a path of observation that gave an optical flow containing dynamic and continuous visual information. The understanding of seeing mechanisms in interior environment can generate a design with better human-interior relation.